2013
DOI: 10.5483/bmbrep.2013.46.8.014
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin ameliorates TNF-α-induced ICAM-1 expression and subsequent THP-1 adhesiveness via the induction of heme oxygenase-1 in the HaCaT cells

Abstract: Adhesion molecules such as ICAM-1 are important in the infiltration of leukocytes into the site of inflammation. In this study, we investigated the inhibitory effects of curcumin on ICAM-1 expression and monocyte adhesiveness as well as its underlying action mechanism in the TNF-α-stimulated keratinocytes. Curcumin induced expression of heme oxygenase-1 (HO-1) in the human keratinocyte cell line HaCaT. In addition, curcumin induced Nrf2 activation in dose- and time-dependent manners in the HaCaT cells. Curcumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 31 publications
1
33
1
Order By: Relevance
“…In the present study, we confirmed that phloretin suppressed the TNF-α-induced translocation of NF-κB into the nucleus, thereby suppressing IL-6, IL-8, MCP-1, MDC, and TREC expression. Previous studies had found that inhibited PI3K-Akt signaling could suppress NF-κB movement into the nucleus in HaCaT cells [7,35]. The MAPK pathways also are important regulatory factors in promoting NF-κB activation [8].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In the present study, we confirmed that phloretin suppressed the TNF-α-induced translocation of NF-κB into the nucleus, thereby suppressing IL-6, IL-8, MCP-1, MDC, and TREC expression. Previous studies had found that inhibited PI3K-Akt signaling could suppress NF-κB movement into the nucleus in HaCaT cells [7,35]. The MAPK pathways also are important regulatory factors in promoting NF-κB activation [8].…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies found that the surface of inflammatory epidermal keratinocytes could express cell adhesion molecules to bind and adhere to infiltrating lymphocytes in the lesional skin of patients with atopic dermatitis [7]. In the lesional skin, infiltrating neutrophils and monocytes could release inflammatory mediators and cause severe skin lesions [31].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Turmeric is a medical plant which is widely used as edible seasoning from its rhizome. Rhizome extract is called curcuminoid and it includes curcumin, dimetixocorquine and dimetixine curcumin base [10]. Curcumin is insoluble in water and ether but dissolves in alcohol, acetic acid, alkaline and some oils, including olive oil.…”
Section: Introductionmentioning
confidence: 99%